2020
DOI: 10.1186/s12876-020-01447-0
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and validation of mucosal TNF expression combined with histological score - a biomarker for personalized treatment in ulcerative colitis

Abstract: Background There are no accurate markers that can predict clinical outcome in ulcerative colitis at time of diagnosis. The aim of this study was to explore a comprehensive data set to identify and validate predictors of clinical outcome in the first year following diagnosis. Methods Treatment naive-patients with ulcerative colitis were included at time of initial diagnosis from 2004 to 2014, followed by a validation study from 2014 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 46 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…Anti-TNF mAbs could significantly reduce the expression level of TNF-α and suppress the inflammation, therefore the changed mucosal TNF-α transcript level might be used as a promising biomarker to assess the anti-TNF efficacy. More recently, we have validated a correlation between mucosal TNF-α transcript levels and response to anti-TNF mAbs in UC [7] . Validation data demonstrated that baseline mucosal TNF-α transcript level was a better biomarker with a high-test reliability for the prediction of clinical outcomes than other clinical parameters e.g., calprotectin, the UC disease activity index (UCDAI) score, Mayo endoscopic score in patients with UC [7] .…”
Section: Novel Putative Biomarkersmentioning
confidence: 81%
See 3 more Smart Citations
“…Anti-TNF mAbs could significantly reduce the expression level of TNF-α and suppress the inflammation, therefore the changed mucosal TNF-α transcript level might be used as a promising biomarker to assess the anti-TNF efficacy. More recently, we have validated a correlation between mucosal TNF-α transcript levels and response to anti-TNF mAbs in UC [7] . Validation data demonstrated that baseline mucosal TNF-α transcript level was a better biomarker with a high-test reliability for the prediction of clinical outcomes than other clinical parameters e.g., calprotectin, the UC disease activity index (UCDAI) score, Mayo endoscopic score in patients with UC [7] .…”
Section: Novel Putative Biomarkersmentioning
confidence: 81%
“…However, they could not validate such correlation between changed microbiota and anti-TNF therapeutic response [46] . More recently, our group have validated the value of mucosal TNF transcript as a reliable biomarker in the evaluation of anti-TNF therapeutic response in patients with UC [7] . We were able to show that baseline mucosal TNF-α transcript level was a better biomarker than other clinical parameters e.g., calprotectin, the UC disease activity index (UCDAI) score, Mayo endoscopic score in patients with UC [7] .…”
Section: Combination Validation and Comparison Studies Between Current And Novel Biomarker In The Evaluation Of Anti-tnf Therapeutic Respmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to serological markers, mucosa derived molecular signatures have also been tested for their disease prognostic value. For example, mucosal TNF-alpha expression combined with histological disease activity scores at the point of diagnosis have been reported to be predictive of a severe outcome in UC with a positive and negative predicate values of 0.89 and 0.87 respectively [ 40 ]. However, such parameters are very difficult to implement in routine clinical practice and results are still pending validation in larger, independent patient cohorts.…”
Section: Existing Biomarkers In Ibdmentioning
confidence: 99%